Fauna Community Structure In Sungai Melaban, Sarawak During Low Tide - Nur Sabiha, binti Mohd Aluwi (Universiti Malaysia Sarawak(UNIMAS), 2013)
This study was conducted to determine the diversity of fish, shrimps, crabs and mollusks community at Sungai Melaban, UNIMAS campus, Sarawak. Fish were sampled during low tide at two sampling stations. Fish were collected using scoop net and cast net. A total of 563 individuals belonging to 12 families and 25 species were collected. This represented 77.26% by family Panaeidae, 6.22 % from Tetraodontidae, 5.86 % from Gobiidae, 4.26 % from Palamonidae, 2.31 % from Eleotridae, 1.07 % each by the family Gerreidae and Ambassidae, 0.71 % from Datnioidae, 0.36 % represented by families Scatophagidae, Cyrenidae and Cynoglossidae, while the remaining 0.18 % was represented by family Synanceidae Based on the sampling result, Sungai Melaban was dominated by family Panaeidae. Most of the fishes caught were in juvenile stage which consists of marine migrant and estuarine species.